Sex differences in high-intensity statin use following myocardial infarction in the United States - Peters, S; Colantonio, L; Zhao, H; Bittner, V; Dai, Y; Farkouh, M; Monda, K; Safford, M; Muntner, P; Woodward, M (Elsevier, 2018)
Background Historically, women have been less likely than men to receive guideline-recommended statin therapy for the secondary prevention of myocardial infarction (MI). Objectives The authors examined contemporary sex differences in prescription fills for high-intensity statin therapy following an MI, overall and across population subgroups, and assessed whether sex differences were attenuated following recent efforts to reduce sex disparities in the use of cardiovascular disease preventive therapies. Methods The authors studied 16,898 (26% women) U.S. adults <65 years of age with commercial health insurance in the MarketScan database, and 71,358 (49% women) U.S. adults ≥66 years of age with government health insurance through Medicare who filled statin prescriptions within 30 days after hospital discharge for MI in 2014 to 2015. The authors calculated adjusted women-to-men risk ratios and 95% confidence intervals (CIs) for filling a high-intensity statin prescription (i.e., atorvastatin 40 to 80 mg, and rosuvastatin 20 to 40 mg) following hospital discharge for MI. Results In 2014 to 2015, 56% of men and 47% of women filled a high-intensity statin following hospital discharge for MI. Adjusted risk ratios for filling a high-intensity statin comparing women with men were 0.91 (95% CI: 0.90 to 0.92) in the total population, 0.91 (95% CI: 0.89 to 0.92) among those with no prior statin use, and 0.87 (95% CI: 0.85 to 0.90) and 0.98 (95% CI: 0.97 to 1.00) for those taking low/moderate-intensity and high-intensity statins prior to their MI, respectively. Women were less likely than men to fill high-intensity statins within all subgroups analyzed, and the disparity was largest in the youngest and oldest adults and for those without prevalent comorbid conditions. Conclusions Despite recent efforts to reduce sex differences in guideline-recommended therapy, women continue to be less likely than men to fill a prescription for high-intensity statins following hospitalization for MI.